Growth and properties of GaAs nanowires on fused quartz substrate - 赵玉峰 李新化 王文博 周步康 段花花 史同飞 曾雪松 李宁 王玉琦 (Journal of semiconductors, 2014)
The growth of GaAs nanowires directly on fused quartz substrates using molecular beam epitaxy via a vapor-liquid-solid mechanism with gold as catalyst is reported. Unlike conventional Au-catalyst MBE growth of nanowires （NWs） on GaAs substrates, zinc blende is found to be the dominant crystal structure for NWs grown on fused-quartz substrates by MBE. Further transmission electron microscopy measurements show that the prepared ZB NWs have the growth direction of [112] and lamellar { 111 } twins extend through the length of NWs. Although there are longitudinal planar defects that extend through NWs, the narrow full width at half maximum of PL implies high crystal quality of NWs grown on fused-quartz substrates.